Self Micro Emulsifying Drug Delivery System - VISHVAJIT A. KAMBLE; DEEPALI M. JAGDALE; VILASRAO J. KADAM (International Journal of Pharma and Bio Sciences, 2010)
Oral route is the main route of drug administration in many diseases. Major problem in oral route of drug administration is bioavailability which mainly results from poor aqueous solubility. This leads to lack of dose uniformity and high intrasubject/intersubject variability. It is found that 40% of active substances are poorly water-soluble. Various technologies are developed to overcome this problem, like solid dispersion or cyclodextrin complex formation. Much attention has been given to lipid-based formulation with particular emphasis on self-micro emulsifying drug delivery system to improve the oral bioavailability of lipophilic drugs. It requires small amount of dose and also drugs can be protected from hostile environment in gut. Self micro emulsifying drug delivery systems are specialized form of delivery system in which drug is encapsulated in a lipid base with or without pharmaceutical acceptable surfactant.